2002
DOI: 10.1002/mop.10219
|View full text |Cite
|
Sign up to set email alerts
|

Planar monopole folded into a compact structure for very‐low‐profile multiband mobile‐phone antenna

Abstract: A planar monopole consisting of three branch strips and folded into a rectangular‐box‐like compact structure for very‐low‐profile GSM/DCS/PCS multiband mobile‐phone antennas is presented. The three branch strips are designed to operate as quarter‐wavelength structures at 900, 1800, and 1900 MHz, respectively, and the obtained impedance bandwidths cover the required bandwidths of the GSM band (890–960 MHz), the DCS band (1710–1880 MHz), and the PCS band (1850–1990 MHz). The proposed antenna has a compact size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…In this Letter a novel dual-band monopole design with an even lower profile than that shown in [2,3] is presented. The planar monopole is first printed on a thin FR4 substrate and then bent into a three-dimensional structure having two equal and perpendicular sections.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this Letter a novel dual-band monopole design with an even lower profile than that shown in [2,3] is presented. The planar monopole is first printed on a thin FR4 substrate and then bent into a three-dimensional structure having two equal and perpendicular sections.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, it has been demonstrated that, by folding the planar monopole into a three-dimensional structure [2,3], reduced antenna height can be obtained, which is very attractive for mobile phone applications. The design reported in [2] showed a folded planar monopole antenna having a wide bandwidth of about 900 MHz, which covers the DCS, PCS, UMTS, and WLAN bands for mobile phone applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antenna can be tuned to operate either in GSM 850, 900 and 1900 bands or GSM 850, 900 and 1800 bands by providing VSWR≤2.5 within the given frequency bands. In another realized antenna (Teng & Wong, 2002), a structure consisting of three meandered lines and wrapped into a compact rectangular box is presented for GSM 900, 1800 and 1900 frequency bands. The proposed antenna covers the required bandwidths of GSM 900, 1800 and 1900 by having VSWR less than 2.5 and gain ranging from 1.4 to 3.6 dBi.…”
Section: Low Profile Antennasmentioning
confidence: 99%
“…However, they often present a narrow bandwidth [13] because of the small distance between the ground plane and the radiating patch. Monopole antennas also received a great interest for an efficient integration of the radiating component in small portable devices, but additional branch structures are usually necessary to yield a multiband behavior [14,15]. Alternative techniques have been also proposed to obtain multiple resonances with a single monopole antenna.…”
Section: Introductionmentioning
confidence: 99%